Cellulosics exhibition display (circa 1950) - Hercules Incorporated (1950)
General view of an exhibition display for cellulose products manufactured and sold by the Hercules Powder Company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Advertising, Industrial; Advertising; Chemical industry; Corporations; Hercules Incorporated; Cellulose; Ethylcellulose; Cellulose industry; Trade shows